ULINASTATIN IN THE CONSERVATIVE THERAPY OF CHRONIC PANCREATITIS - Mirvosit M. Karimov; Pulat S. Zufarov; Go’zal N. Sobirova; Nargiza I. Pulatova; Shahlo S. Aripdjanova (Central Asian Journal of Medicine, 2022)
The article presents the results of the anti-inflammatory efficacy of the new generation protease inhibitor ulinastatin in the treatment of exacerbation of chronic pancreatitis of moderate severity. It is shown that exacerbation of chronic pancreatitis of alimentary, alcoholic and biliary etiology was expressed by abdominal pain and dyspeptic symptoms. An increase in the level of serum aminotransferases, bilirubin and alpha amylase was noted, which was accompanied by a significant increase in the activity of pro-inflammatory cytokines. The use of ulinastatin in the complex of pharmacotherapy of chronic pancreatitis contributed to the effective relief of exacerbation of pancreatitis, which was due to the anticytokine effect of the drug.